Recent Advances in the Delivery, Mechanism of Action and Antibacterial Activity of Silver Nanoparticles - Idris, N. U.; Faruk, F. U.; Yerima, M. I.; Isa, A. K. (UMYU Journal of Microbiology Research)
Study’s Novelty/Excerpt